Implementation of Competency Enhancement Program for Science Teachers Assisted by Artificial Intelligence in Designing HOTS-based Integrated Science Learning - Gunawan, Kadek Dwi Hendratma; Liliasari, Liliasari; Kaniawati, Ida; Setiawan, Wawan (Jurnal Penelitian dan Pembelajaran IPA, 2021)
Education currently supported by technological developments such as artificial intelligence (AI) and robotics. Science learning based on higher-order thinking skills (HOTS) is needed as the main goal in learning. AI in teacher professional developments are the new way to be implemented. The purpose of this research was to describe the competency enhancement program for science teacher that assisted by AI in designing HOTS-based integrated science learning. 29 science teachers in West Java participated in this program. Descriptive analysis was used to analyze the data from all participants. The results revealed that the program held in blended learning with face-to-face sessions about higher order thinking skills in science learning, use of multiple representations in science learning, construct of science learnings’ theme, integrated science learning, and continued by online learning by web based-AI. Science teachers perceived helpfulness to integrate various science content, followed courses, held discussion, answer the tests, and validating lesson plan products. Teachers has new experiences for the implementation program.